The Turkish Version of the Exercise Addiction Inventory: Validity and Reliability - Aydın, Davut; Baltacı, Umay Bilge; Erzen, Evren; Szabo, Attila; Griffiths, Mark D. (Addicta: The Turkish Journal on Addictions, 2023)
Exercise addiction is a growing area of research interest, and many psychometric scales have been devel- oped for its measurement. One of the most widely used instruments is the Exercise Addiction Inventory, which has been translated and validated in several languages but not in Turkish. Therefore, the present study aimed to translate and validate the Exercise Addiction Inventory into Turkish for promoting exercise addiction research in Turkiye. The sample comprised 665 university students with ages ranging from 17 to 47 years [491 females and 174 males; Mage = 21.23 years, standard deviation = 3.16]. A confirmatory factor analysis confirmed the one-dimensional structure of the scale (χ2/df = 2.98, [Goodness of Fit Index] GFI = 0.98, [Comparative Fit Index] CFI = 0.98, [Adjusted Goodness of Fit Index] AGFI = 0.96, [Root Mean Square Error of Approximation] RMSEA = 0.05). The scale’s reliability was very good in terms of both the omega coefficient (0.81) and alpha coefficient (0.80). The Turkish Exercise Addiction Inventory showed good concurrent reliability with the Exercise Addiction Scale and Sport Engagement Scale. These findings sug- gest that the Turkish Exercise Addiction Inventory is a valid and reliable instrument for assessing exercise addiction among Turkish university students.
Keywords: Exercise addiction; Exercise Addiction Inventory; exercise dependence; psychometrics; Turkiye; validation